Semanda Lekok in the Sai Batin Community, Lampung: Wife's Domination of Marital Assets from Maqāṣid al-Sharī’ah Perspective - Firdawaty, Linda; Asnawi, Habib Shulton; Mahmudah, Siti (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
The semanda lekok marriage tradition among the Lampung Sai Batin people results in the wife dominating the husband, particularly in terms of control over marital property. This dominance is a consequence of the semanda marriage, in which wedding expenses and living costs are borne by the wife’s family, and after which the husband lives with the wife’s family. This study aims to analyze the forms of wife’s dominance over the husband in the semanda marriage, the reasons why the Lampung Sai Batin indigenous people maintain the semanda lekok marriage, and the contribution of this tradition to the development of Islamic family law. The study used a qualitative method with an empirical approach. Data came from the primary and secondary data sources. The data were collected by means of interview. The respondents consisted of the husbands in semanda lekok marriages, customary leaders, and religious leaders in Pekon Bakhu, Batu Ketulis Subdistrict, West Lampung. The data analysis involved the theories of Maqāṣid al-Sharī’ah and gender justice. The findings reveal that the forms of wife’s dominance include the husband being severed from his nasab (lineage) and inheritance rights from his parents, the husband not being entitled to joint earnings, and inherited property being granted to the eldest son. However, there has been a shift in values in the practice of semanda inheritance law; when the wife dies and the couple has no children, the husband receives a share of the inheritance. The reason for maintaining this marriage system is to continue the lineage of the wife’s family as her parents do not have a son and the wife is the only child, as well as the wife’s family has the economic ability and is a solution for prospective husbands who cannot afford the marriage. Nevertheless, the tradition of denying joint property distribution is contrary to the Maqāṣid al-Sharī’ah and gender justice. Therefore, it is important to adapt and negotiate in implementing the semanda lekok marriage to maintain the objectives of sharia and the values of gender justice.